2015
DOI: 10.1371/journal.pone.0117732
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Outer Membrane Proteome and Secretome of Bacteroides fragilis Reveals a Multiplicity of Secretion Mechanisms

Abstract: Bacteroides fragilis is a widely distributed member of the human gut microbiome and an opportunistic pathogen. Cell surface molecules produced by this organism likely play important roles in colonization, communication with other microbes, and pathogenicity, but the protein composition of the outer membrane (OM) and the mechanisms used to transport polypeptides into the extracellular space are poorly characterized. Here we used LC-MS/MS to analyze the OM proteome and secretome of B. fragilis NCTC 9343 grown un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 81 publications
1
64
0
Order By: Relevance
“…Johnson, Sikora, Zielke, & Sandkvist, 2013;Renier et al, 2015;Zijnge, Kieselbach, & Oscarsson, 2012). These maps supported the evaluation of signal peptide algorithms (Leversen et al, 2009) and even suggested the presence of yet-unknown peptide transport systems (Wilson, Anderson, & Bernstein, 2015).…”
Section: Assembly Of Bacterial Respiratory Complexessupporting
confidence: 67%
“…Johnson, Sikora, Zielke, & Sandkvist, 2013;Renier et al, 2015;Zijnge, Kieselbach, & Oscarsson, 2012). These maps supported the evaluation of signal peptide algorithms (Leversen et al, 2009) and even suggested the presence of yet-unknown peptide transport systems (Wilson, Anderson, & Bernstein, 2015).…”
Section: Assembly Of Bacterial Respiratory Complexessupporting
confidence: 67%
“…To determine whether the LES identified in C. canimorsus would be conserved in other Bacteroidetes , we took advantage of the recently published B. fragilis NCTC 9343 surfome study (44) and performed an in silico analysis on the N termini of the identified surface lipoproteins (see Fig. S5A in the supplemental material).…”
Section: Resultsmentioning
confidence: 99%
“…3A; Dataset S1, Table S4). Three of these proteins are homologs of the secreted proteobacterial T6SS structural proteins Hcp [also observed in a recent study (16)] and VgrG, and the fourth contains a PAARrepeat domain typical of T6SS adaptors (9,10). Of the two remaining proteins, BF9343_1937 lacks any known T6S effector domains, and BF9343_1928 contains a MIX domain found in other T6SS effectors (17).…”
Section: B Fragilis Strains Encode Extensive Variation In Effector/imentioning
confidence: 69%